POLA KOMUNIKASI IBU SINGLE PARENT DALAM MENDIDIK ANAK USIA REMAJA DI MOJOKERTO - Putri, Salsabila Karina; S.Sos., M.I.Kom., Mutiah (The Commercium, 2024)
In 2022, there will be 4,253 couples in Mojokerto who will divorce, the causes are quarrels, economicproblems, polygamy and apostasy. Jetis District in Mojokerto has the highest divorce rate, which has animpact on the increasing number of single parents. Divorce not only has an impact on husband and wife,but also on children, especially teenagers. The impact includes feelings of insecurity, loneliness, andfeelings of guilt in children. Researchers used a qualitative approach with phenomenological methodsand three communication patterns, namely, Authoritarian, Authoritative, and Permissive. The researchresults showed that of the 6 single parents studied, the family communication patterns applied varied,including Authoritarian, Authoritative, and Permissive. This research aims to understand how singleparent mothers' communication patterns influence their relationships with their teenage children and theformation of teenagers' self-concept. In facing the challenging teenage years, effective communicationbetween single parents and children is very important to ensure healthy development and a goodrelationship between the two. The research results showed that of the 6 single parents in Jetis, Mojokerto,there were variations in the family communication patterns they adopted. Most use authoritative patterns which have been proven to be effective in educating teenagers. proven authoritative, suitable for use bysingle parents educating teenage children.